2018
DOI: 10.1002/chem.201801444
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable and Red‐Emitting Nanovesicles Incorporating Lipophilic Diketopyrrolopyrroles for Cell Imaging

Abstract: Diketopyrrolopyrroles (DPPs) have recently attracted much interest as very bright and photostable red-emitting molecules. However, their tendency to form nonfluorescent aggregates in water through the aggregation-caused quenching (ACQ) effect is a major issue that limits their application under the microscope. Herein, two DPP molecules have been incorporated into the membrane of highly stable and water-soluble quatsomes (QS; nanovesicles composed of surfactants and sterols), which allow their nanostructuration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Regarding the impact of ionic strength, in both cases, the addition of 1 ml of phosphate buffered saline to 1 ml of ONP suspension (nal salt concentration: phosphate buffer 0.01 M, KCl 0.0027 M, NaCl 0.137 M) did not induce any precipitation at least for one week. Contrarily with what we observed in our previous studies on triazole-thiophene-DPP ONPs, 14,15 where the J-aggregation was associated with a poor colloidal stability and with a remarkable tendency to aggregation, DPP4T-CH 2 SAc ONPs possess a high colloidal stability (observed also for the other derivative). Moreover, the presence of -SAc terminal group induces the formation of NIR emitting J-aggregates, opening the way to a promising system for the in vitro and in vivo bioimaging.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Regarding the impact of ionic strength, in both cases, the addition of 1 ml of phosphate buffered saline to 1 ml of ONP suspension (nal salt concentration: phosphate buffer 0.01 M, KCl 0.0027 M, NaCl 0.137 M) did not induce any precipitation at least for one week. Contrarily with what we observed in our previous studies on triazole-thiophene-DPP ONPs, 14,15 where the J-aggregation was associated with a poor colloidal stability and with a remarkable tendency to aggregation, DPP4T-CH 2 SAc ONPs possess a high colloidal stability (observed also for the other derivative). Moreover, the presence of -SAc terminal group induces the formation of NIR emitting J-aggregates, opening the way to a promising system for the in vitro and in vivo bioimaging.…”
supporting
confidence: 83%
“…12,13 In our previous works we observed that varying the length of terminal aliphatic side chains (C 8 vs. C 16 ) in a donor-acceptor-donor (DAD) triazole-thiophene-DDP derivative, it was possible to induce the formation of H-or J-aggregates in thin lms and organic nanoparticles (ONPs). 14,15 Especially, we found that, for both the C 8 and C 16 substituted molecules, H-aggregates were preferentially formed during the self-assembly, but in the case of C 8 substituted species, the resulting ONPs were characterized by low colloidal stability with a remarkable tendency to form micrometric rod-like particles. This morphological evolution of ONPs was associated to an enhancement of the J-aggregate absorption, demonstrating the importance of terminal aliphatic chains in the supramolecular organization of the dye.…”
mentioning
confidence: 89%
“…Finally, the cellular penetration capability of different types of fluorescent QSs in different cell lines has been also reported. [32][33][34][35] In this respect, introducing responsiveness to external molecular inputs within fluorescent QS nanovesicle could pave the way for the rational design of multifunctional biomimetic vesicles capable of translating the recognition of target molecules into signal transduction for biosensing applications. Motivated by the above considerations, here we anchor fluorescent cholesterol-modified DNA probes (i.e., F-miRNA probe) on dye-loaded QSs, to produce FRET-active nanovesicles responsive to clinically relevant nucleic acid targets such as microRNAs (miRNA), a class of small endogenous non-coding RNAs that can be used as diagnostic and prognostic markers in multiple human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The components mostly used are cationic lipids such as DOTMA (trimethyl [2,3-(dioleyloxy) propyl] ammonium chloride) or DPPC (DL-dipalmitoylphosphatidylcholine) and the nonionic sorbitan monostearate or trioleate, which resemble the structure of phospholipids that form biological membranes [28,29]. The choice of nanovesicle type affects the final shape and thickness of the membrane as well as supramolecular reorganization, permeability, elasticity and compatibility with biological materials [30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%